Help Desk Application Program at PT. X In Web-Based Jakarta - Amelia Amelia (Journal of Business Social and Technology, 2021)
X is a telecommunications company in Indonesia, PT X itself started its commercial operations since October 8, 1996 and until now PT. X itself already has a working permit system, but in the system itself there is no place to submit complaints contained in a building and certain parts, so if there is damage or disruption to the building takes a long time, because during this time if there is damage to the building is not controlled directly by the supervisor directly so that in the data collection of building assets that have undergone replacement or repair is not controlled by the supervisor Efforts carried out by the author to gather information relevant topics and issues that will or are being researched. The information can be obtained from scientific books, research reports, scientific papers, thesis and dissertations, regulations, statutes, yearbooks, encyclopedias and written sources both printed and electronic and internet.